Penggunaan LKPD berbasis Peer Tutoring dalam Cooperative Learning untuk Meningkatkan Hasil Belajar Peserta Didik di Sekolah Dasar - Rafido Azuri; Ujang Efendi; Annisa Rahmah; Adelia Mawarni; Supriyadi; Jody Setya Hermawan (Universitas Muhammadiyah Kuningan, 2025)
The purpose of this study was to determine the effect of using Peer Tutoring-based LKPD on the learning outcomes of grade V students of Elementary School 3 Gedong Aer, Bandar Lampung City in the 2023/2024 academic year. This study is a quantitative study using Quasi Experimental Design and Pretest-Posttest Control Group Design. Data collection techniques in this study include interviews, observations, and tests of students' Indonesian language learning outcomes. The analysis techniques used are descriptive statistics and t-tests. Based on the results of the t-test on the increase in student learning outcomes 0.00 <0.005, and with an N-gain of 0.00, it meets the fairly effective category. So it can be concluded that Peer Tutoring-based LKPD can improve the Indonesian language learning outcomes of grade V students of Elementary School 3 Gedong Aer, Bandar Lampung City, so that students can be more active during learning by using Peer Tutoring-based LKPD on Indonesian language material, namely understanding Procedural Texts.